The management of pluralism, democracy and national security in Malaysia: implications for Southeast Asia and the broader Asia-Pacific region - Ra'ees, Wahabuddin (2011)
This paper investigates the linkage between Islam, democracy and security in plural societies. The paper assumes that the major challenge in plural societies is ethnic rivalry with potential security threat to their internal cohesiveness and regional stability. The intensity of the challenge is closely related to the degree of religious, racial, cultural and linguistic diversity. The more diverse a society is in terms of religious, racial, linguistic and class divisions the more unstable it can become through bad strategic management, as these elements can reinforce each other and reduce the chances of integration, peaceful co-existence and harmonious relations among the various ethnic groups. This study examines Malaysia’s approach to managing intra-ethnic relations and relations among its various ethnic communities. In analyzing intra-ethnic relations, this study focuses on the absence of radical tendencies among the Malay political parties. The Malays are the dominant ethnic group in Malaysia. The Malays, despite being followers of the religion of Islam, do not possess a common political orientation. Yet, the relations among the different Malay parties and groups, like other Muslim societies in the Middle East, have not been radicalized. In analyzing inter-ethnic relations, this study argues that the Malay dominated government’s management of ethnic relations in Malaysia and its ability to hold to a relative peaceful co-existence has been an experiment that other Muslim nations could learn from. But Malaysia would need to do more to integrate its various ethnic groups to realize Prime Minister Najib’s 1 Malaysia policy. Finally, the paper attempts to examine the strategic implications of Malaysia’s approach to, and management of pluralism for national as well as regional security in Southeast Asia. It will indicate any possible lessons to be learned for the management of ‘plural society’ in a democratic system as in Malaysia and Australia.